Outcomes following persistent atrial fibrillation ablation using localized sources identified with Ripple map. (7th August 2019) - Melby, Daniel P.; Gornick, Charles; Abdelhadi, Raed; Sengupta, Jay; Pai, Manju; Zakaib, John S.; Moore, JoEllyn; Benditt, David G.
Abstract: Background: Ablation of persistent atrial fibrillation (AF) remains challenging. Identification and ablation of localized AF drivers may offer the possibility for improved outcomes. Ripple map is a novel software algorithm that may allow improved localization of possible AF drivers through the whole chamber graphical display of continuously recorded bipolar electrograms. The objective of this study was to determine whether regions of high‐frequency Ripple activation (HFRA) observed on Ripple map provide useful ablation targets in patients with persistent AF. Methods and Results: Consecutive patients underwent the first‐time ablation of persistent AF (n = 162) using a standard stepwise (n = 105) or a Ripple map guided approach (n = 57). Ripple map guided patients underwent pulmonary vein antral isolation followed by ablation of HFRA sites. Acute termination of AF was observed in 91.2% of the Ripple‐guided patients vs 52.4% in the stepwise approach, P  < .0001. Following a single ablation procedure, after 18 months 98.2% of Ripple map guided patients were free of AF, compared with 81.4% of standard stepwise ablation ( P  = .005). Freedom from atrial tachycardia (54.4% Ripple map vs 52.4% standard, P  = .9) or any atrial arrhythmia (52.6% Ripple map vs 39.0% standard, P  = .10) did not differ between the two strategies. In a subset analysis (n = 30 of 56), Ripple map regions corresponded to sites with spatiotemporal dispersion in all atrial locations. No differences were observed in the rate of procedural complications. Conclusions: Ablation of HFRA sites identified with Ripple map resulted in a higher rate of acute termination and improved freedom from AF compared to a standard stepwise approach.